Effect of Hot-Air Drying and Vacuum Drying on Oxalate Contents of Limnophila Aromatica and Limnophila Geoffrayi - Wanyo, Pitchaporn; Huaisan, Kannika; Boothaisong, Supattra; Nitisuk, Panorjit; Wongpreedee, Panida; Chamsai, Tossaporn (Food and Applied Bioscience Journal, 2017)
This study investigated the total, soluble and insoluble oxalate contents of two rice paddy herbs (Limnophila aromatica and Limnophila geoffrayi) as affected by hot-air and vacuum drying methods at different temperatures (50, 60, 70, and 80°C). Overall, the lowest content of soluble oxalate was observed which a high temperature (70 and 80°C) of hot-air dried samples (3.47 and 3.14 mg/g DW in L. geoffrayi and 11.39 and 11.75 mg/g DW in L. aromatic, respectively), while soluble oxalate content was highest in the high temperature (80°C) vacuum dried samples (5.84 mg/g DW in L. geoffrayi and 18.23 mg/g DW in L. aromatica, respectively). With an increase in drying temperature, there was significantly decreased soluble oxalate content in the hot-air dried samples, while oxalate content increased in the vacuum dried samples. Total oxalate contents had slight changes with the same trend for soluble oxalates. On the other hand, insoluble oxalate content showed a contrasting effect with the soluble and total oxalate content. In addition, the results showed that the soluble and total oxalate contents for various drying temperatures for the L. geoffrayi species were significantly lower than for the L. aromatica species. Hot-air drying at 70°C provided the optimal results with respect to the content of soluble oxalates.